The Need for the Optimization of HIV Antiretroviral Therapy in Kazakhstan - Aidana Mustafa; Natalya Dzissyuk; Bauyrzhan Bayserkin; Dinara Begimbetova; Zhamilya Nugmanova; Syed Ali (Viruses)
The number of people living with HIV in Kazakhstan increased from 11,000 to 35,000 between 2010 and 2021, with emerging antiretroviral therapy (ART) resistance posing a challenge to effective treatment. Unsafe injection practices among people who inject drugs (PWID), the stigma against men who have sex with men, sex work, drug possession, HIV transmission, HIV exposure, and the non-disclosure of HIV status create obstacles to effective prevention and care. Our recent studies with people living with HIV (PLWH) in Kazakhstan have revealed the prevalence of mutations in HIV that may confer resistance to certain ART components currently being administered in the country. Additionally, subtype A6- and CRF02_AG-infected PLWH displayed the occurrence of certain distinct subtype-specific DRMs. Subtype A6 exhibited a tendency for the DRMs A62V, G190S, K101E, D67N, and V77I, whereas CRF02_AG was more associated with S162A, K103N, and V179E. Both subtypes had a comparable frequency of the M184V mutation and displayed similar patterns in the distribution of Q174K. Based on our findings, we recommend that DRM screening and subtype diagnosis before the initiation of ART will improve treatment efficiency while preventing the emergence of further DRMs in Kazakhstan.